Surfaces with mean of the hyperbolic curvature radii of double harmonic type - Armando M. V. Corro; Carlos M. C. Riveros; Raquel P. de Aráujo (Selecciones Matemáticas)
In this paper, we define surfaces with mean of the hyperbolic curvature radii of double harmonic type (in short DHRMC-surfaces) in the hyperbolic space, these surfaces include the generalized Weingarten surfaces of the harmonic type (HGW-surfaces). We give a characterization of DHRMCsurfaces. Given a real function, we will present a family of DHRMC-surfaces that depend on two holomorphic functions. Moreover, we classify the DHRMC-surfaces of rotation.